Improving Mathematical Creativity through Problem Posing Learning Model of Algebra in Junior High School (PRISMA, Prosiding Seminar Nasional Matematika, 2020)
Nowadays mathematical creativity is important either for students or teacher and it is low in among students because the students tend to be passive, they only accept what the teacher conveys in learning process. One of the important thing that can be influenced the learning process is the learning model. The alternative learning model is the problem posing model. The purpose of this article is describing how to improve mathematical creativity through problem posing learning model in junior high school students. This research is using study literature of the researchers about the increment of mathematical creativity after implementing problem posing learning model especially in algebra material. Based on the results in study literature, it is known that there is a significant increment of mathematical creativity by using problem posing learning model. If compared with the other learning models, such as mind mapping and student scientific approach, in the problem posing learning method is more effective to improve mathematical creativity.